Alterations of Thyroid Hormone Levels in Children with Intellectual Disability - Zhao, Zhengqin; Su, Min; Wang, Dong; Ye, Jing; Wang, Xiao-na (Neuropediatrics, 2022)
Background The aim of this article was to study the thyroid hormone levels in children with intellectual disabilities and determine the relationship between the thyroid hormone levels and intellectual disability.Methods Participants included 60 children with intellectual disabilities (the study group) and 56 without (the control group). Nuclear medicine in vitro analysis techniques were used in this study. All the controls and patients underwent in vitro analysis, and their serum levels of thyroid hormone, including thyroid-stimulating hormone, total thyroxine (T4), free T4 (FT4), total triiodothyronine (T3), and free T3 (FT3), were tested.Results The levels of FT4 were lower in the study group than in the control group (p < 0.001). The levels of FT3 were higher in the study group than in the control group (p = 0.003). The levels of TSH were higher in the study group than in the control group, but the difference was not statistically significant (p = 0.363). The total T4 and total T3 levels were lower in the study group than in the control group, but the difference was not statistically significant (p = 0.642, p = 0.124, respectively).Conclusion The levels of thyroid hormones in the study group differed from the control group. The differences may not be clinically significant beyond their statistical significance. Thyroid hormone levels may affect intellectual disability in children.
Keywords: thyroid hormone levels; children; intellectual disability